Detection of Avian Influenza Virus H5 and H9 Subtypes in Rural Live Bird Markets at High-Risk Border Areas in Ghana: Implications for Integrated Surveillance - Mensah, Fiona Nana Yaa; Emikpe , Benjamin Obukowho; Folitse, Raphael Deladem; Odoom, Theophilus; Tweneboah, Albert Agyapong; Sarpong, Kofi (Universitas Airlangga, 2026)
The frequency of highly pathogenic avian influenza outbreaks in Ghana and neighbouring countries require the detection of avian influenza virus subtypes H5 and H9 in local poultry at live bird markets (LBMs) in border areas. Using real-time reverse-transcription polymerase chain reaction (RT-qPCR), we analyzed 770 samples from local chickens, guinea fowl, and ducks across four border live bird markets. Samples were screened for influenza A virus (Ct<35). Prevalence by sample type, location, and species was calculated at 95% confidence. Of the 770 samples, the prevalence of influenza A was 6.4% (CI: 4.7–8.3). Tracheal swabs showed a higher prevalence (8.8%; CI: 6.2–12.1) than cloacal swabs (3.9%; CI: 2.2–6.3). Similarly, Southern Ghana showed a higher prevalence (11.2%; CI: 7.4, 16.0) than in Northern Ghana (4.4%; CI: 2.8, 6.5) (p<0.05). Further subtyping of the M-gene-positive samples confirmed the circulation of H5 [4.4% (CI: 2.6, 7.0)] and H9 [2.9% (CI: 1.4, 5.1)] in all four live bird markets from the two locations. This study highlights the need for transboundary surveillance of H5 and H9 viruses, improved biosecurity, and policy interventions in border live bird markets to reduce the maintenance and transmission of AIVs in Ghana.